Socio-emotional processes during the COVID 19 pandemic in graduate students - López Sánchez, Oliva (2023)
Introduction: The changes in the academic life of graduate students due to the pandemic generated complex socioemotional processes that need to be explored. Objective: to compare the socioemotional processes in graduate students during the closure of universities according to the area of knowledge and sex. Method: exploratory-descriptive-comparative quantitative study with a cross-sectional design. A total of 119 questionnaires were analyzed using the Mann-Whitney U non-parametric statistical test to determine significant differences in the independent variables. Results: Significant differences were identified before and during the pandemic in prosocial emotions and mood affectations in both groups of students due to the overload of academic-work activities and the differentiated conditions by area. Women in area 2 were more affected. Discussion: the socio-structural and situational context and the educational level condition socioemotional processes in a statistically significant way. Scope and limitations of the study are discussed.